Just The Two of Us: Dyadic Analysis Parenting Stress and Marital Satisfaction in the Transition to New Parenthood - Salsha Istari; Sri Redatin R. Pudjiati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The consequences of transitioning to parenthood vary from individual to individual and can impact the quality of marriages. This study aims to analyze the role of parenting stress on marital satisfaction from the perspective of individuals and couples using the Actor-Partner Interdependence Model (APIM) approach. This study used a correlational quantitative method with measurements based on Structural Equation Modelling (SEM) on 132 married couples who were transitioning to new parenthood (age of the first child 0–2 years). The results showed a significant actor effect, where parenting stress hurt marital satisfaction in both husbands (β = –0.932, p < 0.001) and wives (β = –0.902, p < 0.001). From the aspect of partner effect, it was found that the stress of the wife's parenting has a significant impact on the husband's marital satisfaction (β = –0.377, p = 0.004), while the husband's parenting stress did not have a substantial effect on the wife's satisfaction (β = –0.282, p = 0.175). These findings indicate that emotional dynamics and parenting burdens not only impact individuals but also affect relationships within couples in an unbalanced way. This study emphasizes the importance of emotional support and fathers' involvement in parenting to maintain the quality of marital relationships in the early stages of parenting. Keywords: marital satisfaction, parenting stress, APIM, parenting transition